Sonochemistry Synthesis of Lanthanum Ions-Doped Polyaniline/Montmorillonite Nanocomposites and Their Conductivity and Thermostability Characterization - Mo, Zunli; Zhang, Chun; Zhao, Guoping; Zhang, Ping; Wu, Yingbing (Asian Journal of Chemistry, 2015)
A new network structure nanocomposites consisting of polyaniline (PANI), montmorillonite (MMT) and La3+ have been successfully synthesized sonochemically at normal pressure, the as-prepared products have been characterized by transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA) and four-probe method. The test results show that the composites have a unique conductivity and flame resistance. The factors affecting the reaction process were discussed. Furthermore, the mechanisms of phase formation and morphology control of lanthanum ions-doped polyaniline/MMT nanocomposites during the ultrasonic synthesizing process are proposed and discussed.